APLIKASI ONLINESHOP PADA WARUNG AKSESORIS BERBASIS WEB DAN MOBILE MENGGUNAKAN METODE TOPSIS - Putri Shafira; Bagus Mulyawan; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Onlineshop Applications On Warunk Accessories Web-Based and Mobile Using Topsis Method is an application that aims to facilitate the process of selling, recording products and decision support in the selection of suppliers at Warunk Accessories Stores. Applications are used by owners to assess suppliers using Topsis methods and store staff to manage Warunk Accessories stores online and customers to see what products are sold in Warunk Accessories stores, and place orders online. Applications are designed using the PHP and Android programming languages. Application design method using System Development Life Cycle by using Waterfall model. The test results were conducted using User Acceptance Test method and user satisfaction test using questionnaire. With this application can simplify the process of recording data items and buying and selling at Warunk Accessories store. Testing is done using 3 supplier data, after testing the results obtained for the highest value through the system 0.7959 and 0.795 manual. From the test results can be concluded that the application has been running according to the design and the results of application calculations with Topsis method there is little difference with the results of manual calculations.